Effectiveness of the use of WhatsApp for Dissemination of Ideas of Improved Crop Production Techniques - , Neha Sharma, S.K. Chaturvedi, Abhimanyu Chaturvedi, Rashmi Shukla (Archives of Current Research International, 2024)
Across India, WhatsApp groups are not only connecting farmers to their customers in the virtual market, but they’re also creating a network of resources and support for the country’s farmers who need it most. It is one of the world’s most popular communication applications in the 21st century. Therefore, a study on the effectiveness of WhatsApp for the dissemination of agricultural technologies in Paddy Crop was conducted at Krishi Vigyan Kendra, Jabalpur (M.P.), in 2022. An exhaustive WhatsApp user list was prepared from 06 villages: Khiriya Kalan and Kathoda from Panagar block, Badkhera and Dunda from Kundam Block, and Agasi and Ahrora from Sahpura block were selected randomly. Thus, 50 farmers from the three blocks of the district using WhatsApp were selected randomly and grouped to send messages about agricultural aspects. The present study highlights and examines the usefulness of WhatsApp among farmers. The social media–enabled WhatsApp is helping farmers solve farming-related problems more efficiently by making them digitally literate. It can be concluded that by using WhatsApp, farmers can seek information on farm operations and clarify their doubts about agriculture and paddy crop production technology, disease & insect pests, etc. It also saved time and money needed to solve the problems. They perceived in the study that the WhatsApp messages used were clear and satisfactory for them. KVK could have achieved immediate solutions to the farmers on a mass level through this App, and need & time-based services to the farming communities were served. On the level of daily interaction, the WhatsApp groups are successful in providing complete assistance and motivating farmers.